Methodological study on coal-based microbial modification of mineral black clay to overcome plant growth challenges on open-pit mine dumps in cold regions - María Laura Gigena; Dong Xiao; Fangzhou Li; Chengyu Wu; Yuhong Zhang (MethodsX)
A critical challenge in ecological restoration of open-pit mine dumps in cold regions with limited topsoil resources is how to rapidly mitigate the plant growth-inhibitory effects of mineral black clay, thereby converting it into arable soil. Leveraging the high degradation capacity of coal seam-associated microorganisms on fossil carbon materials, combined with soil conditioning techniques, this study developed a microbial-based approach for modifying black clay. Seed germination experiments informed both laboratory and field trial designs. This approach focused on removing germination-inhibiting compounds, establishing a plant-compatible soil ecological environment, and employing composite strategies to reduce soil viscosity. Field experiments demonstrated that in-situ microbial modification of black clay effectively supports ecological restoration, enhances plant growth. To refine and implement this microbial-based bioremediation strategy in practical ecological restoration efforts, two key technical methods were employed: • A comprehensive experimental protocol was established for black clay bioremediation, covering both laboratory-scale and field test procedures, ensuring the approach can be readily adapted to diverse environmental conditions. • By incorporating the characteristics of local species, employing representative seed germination tests to assess plant compatibility can facilitate a rapid evaluation of the bioconversion of mineral substrates into arable soils.